FEATURES OF MODERN SOCIAL RELATIONS IN THE AGRICULTURAL SPHERE AS AN OBJECT OF STATE REGULATION - Soloshenko , Ruslan (Global Prosperity, 2024)
The article presents scientific provisions regarding the clarification of the features of modern social relations in the agrarian sphere as an object of state regulation based on theoretical analysis. It is shown that the progressive development of agriculture and the agrarian sphere in general, including the development of the village as a system of life organization, is possible only under the condition that the existing social system includes the agrarian system in specific forms corresponding to its nature, i.e. in a certain sense, it adapts to the agricultural sphere. In this regard, it is necessary to search for ways and forms of reproduction of agrarian relations, the socio-economic content and specific forms of which would reflect the modern level of agricultural agro-industrial production, their economic connections and fit into the general process of the development of society. It was determined that the development of social relations in the agrarian sphere is influenced by natural and economic factors of the external and internal environment known in science. At the same time, if they are considered in relation to the formation of an organizational and economic mechanism in crisis conditions, the consideration and implementation of these factors becomes especially important in the case of a deepening agrarian crisis. The critical threshold of any of the factors of the external and internal environment determines the level of bankruptcy and crisis of agro-industrial complex entities. It is substantiated that the current tasks of sustainable development require the creation of an effective structure of territorial economy, the basis of which is complexity, for the subjects of state regulation. The formation of a multi-system economy contributes to the dynamic development of agriculture. It is emphasized that during the years of reforms, advantages of individual forms of ownership and organizational and legal forms of management have not been revealed. But the role of large commodity farms was constantly growing. Integrated structures with a closed cycle of production - processing - sale of products also function successfully: agroholdings, agroconsortiums, agrofirms, associations of farms. Studies show that in institutional transformations, for the preservation of a multi-system economy, it is necessary to focus on the unification of economic entities with a predominance of cooperative forms of organization.